Artificial intelligence in colposcopic examination: A promising tool to assist junior colposcopists - Wu, Aiyuan; Xue, Peng; Abulizi, Guzhalinuer; Tuerxun, Dilinuer; Rezhake, Remila; Qiao, Youlin (Frontiers in Medicine, 2023)
Introduction: Well-trained colposcopists are in huge shortage worldwide, especially in low resource areas. Here we aimed to evaluate The Colposcopic Artificial Intelligence Auxiliary Diagnostic System (CAIADS) to detect abnormalities based on digital colposcopy images, especially focus on its role in assisting junior colposcopist to correctly identify the lesion areas where biopsy should be performed. Materials and Methods: This is a hospital-based retrospective study, which recruited the women who visited colposcopy clinics between September 2021 to January 2022. 366 out of 1146 women with complete medical information recorded by senior colposcopist, and valid histology results were included. Anonymized colposcopy images were reviewed by CAIADS and a junior colposcopist separately, and the junior colposcopist reviewed the colposcopy images with CAIADS results (named CAIADS-Junior). The diagnostic accuracy and biopsy efficiency of CAIADS and CAIADS-Junior were assessed in detecting CIN2+ (cervical intraepithelial neoplasia grade 2 or worse), CIN3+, and cancer in comparison with the senior and a junior colposcipist. The factors influencing the accuracy of CAIADS were explored. Results: For CIN2+ and CIN3+ detection, CAIADS showed the sensitivity at ~80% which was not significantly lower than senior colposcopist (for CIN2+: 80.6% vs 91.3%, p=0.061 and for CIN3+: 80.0% vs 90.0%, p=0.189). The sensitivity of junior colposcopist was increased significantly with assistance of CAIADS (for CIN2+: 95.1% vs 79.6%, p=0.002 and for CIN3+: 97.1% vs 85.7%, p=0.039), and were comparable to those of senior colposcopist (for CIN2+: 95.1% vs 91.3%, p=0.388 and for CIN3+: 97.1% vs 90.0%, p=0.125). In detecting cervical cancer, CAIADS achieved the highest sensitivity at 100%. For all endpoints, CAIADS showed the highest specificity (55%–64%) and positive predictive values compared to senior and junior colposcopist. When CIN grades became higher, the average biopsy numbers decreased for the subspecialists and CAIADS required minimum number of biopsies to detect per case (2.2-2.6 cut-points). Meanwhile, the biopsy sensitivity of junior colposcopist was the lowest, but CAIADS assisted junior colposcopist to achive a higher biopsy sensitivity. Conclusion: CAIADS could assist junior colposcopist to improve the diagnostic accuracy and biopsy efficiency, which might be a promising solution to improve cervical cancer screening quality in low resource settings.